Supercritical CO2 , a clean alternative to traditional methods of processing polymeric biomaterials: Superkritični CO2, čistejša alternativa tradicionalnim metodam procesiranja polimernih biomaterialov - Aionicesei, Elena; Škerget, Mojca; Knez, Željko (Acta Medico-Biotechnica, 2021)
A wide variety of natural and synthetic polymers have applications in biomedical devices. They are usually processed by melting or by using organic solvents, but these methods may affect the efficiency of incorporating delicate bioactive compounds, such as drugs and proteins, during polymer processing. These shortcomings can be avoided by using supercritical fluids as processing solvents or plasticizers. Supercritical carbon dioxide (scCO2 ) has attracted attention for its potential as a plasticizer in polymer processing. It is used for obtaining microspheres, microcapsules, foams, membranes and polymer/drug composites. The method offers important advantages over other techniques, including the absence of harmful organic solvents, the mild processing conditions, and the ready control of particle and foam morphology simply by varying pressure and temperature. ScCO2 may also represent a viable alternative to conventional sterilization processes for medical devices. Because the requirements of the field of biomaterials are specific and increasing with time, the technique of polymer processing with scCO2 may represent a promising alternative to classical methods of obtaining controlled delivery systems and tissue engineering scaffolds.
Keywords: supercritical CO2; polymeric biomaterials; polymeric foams; microparticles; composite materials